Pengembangan Instrumen Penilaian Berbasis Higher Order Thinking Skills Berbantuan Aplikasi "Kahoot!" Pada Kompetensi Dasar Menerapkan Penanganan Surat Masuk Dan Surat Keluar Jurusan OTKP Di SMK Negeri 2 Buduran - Kunuzil Jannah; Triesninda Pahlevi (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
This study aims to develop assessment instruments based on higher order thinking skills aided by Kahoot! on the basic competencies of applying the handling of incoming and outgoing letters, analyzing the appropriateness of assessment instruments based on the higher order thinking skills developed, analyzing students 'high-level thinking skills, analyzing students' responses to the use of the Kahoot! application, and knowing the strengths and weaknesses of the Kahoot! application. This study uses Sugiyono's development model with 7 steps of development.. The research subjects consisted of 73 class X students majoring in OTKP SMK Negeri 2 Buduran. The assessment instruments developed were in the form of 20 multiple choice questions. Based on the results of the study, the validity of the assessment instruments was more than 0.227 and the reliability was 0.714. The assessment instruments have also fulfilled the test of the difficulty level of the questions, the differentiation of the questions, and the question deception. The average high-level thinking ability of students is in the "good" category and students give a "very positive" response to the use of Kahoot! by 96%. Kahoot's strength! among others, have an interesting appearance and background music, and there are variations in the form of quizzes. As for Kahoot's shortcomings! among others, the choice of answers consists only of 4 options and there are limited characters in filling in the questions and answers.